OPTIMIZATION ANALYSIS OF PLANT LANDSCAPES IN TANDAI IRRIGATION AREA, KERINCI DISTRICT, JAMBI - Acep Hidayat; Marcellino Rico Ariana (Neutron, 2020)
The Plantation Network has a land area of ​​375 ha. Population which is directly proportional to the necessities of life, one of which is in the food sector, has made the government take the initiative to meet the needs and welfare of the community with productive agricultural land and fields. The data includes secondary data on 10-year rainfall from Depati Parbo and Kayu Aro Station and 10-year climatology from Kayu Aro Climatology Station. The calculation method used is the rainfall intensity Average method, Evapotranspiration modification Penman method, Debit danalan DR.FJ Mock method, cropping patterns, and irrigation water needs. Related to the calculation of 6 alternative cropping patterns with different types of plants and different initial planting plans by making comparisons with the existing discharge factor (Q80). Obtained that the cropping pattern is very possible, namely using the cropping pattern PADI-PADI-PALAWIJA. The most efficient and optimal planting pattern is that this cropping system consists of PADI-PADI-ON with large water demand in tertiary plots (NFR tertiary plots) producing 0 - 1,308 ltr / sec/ha with a maximum of 1,308 ltr / ha / February II, while the need for irrigation water in the intake (DR intake) ranges from 0 - 1,615 ltr sec/ha with a maximum of 1,615 ltr / sec/ha in February II. The available debit and debit in the Irrigation Network Planning Mark is very abundant with the mainstay discharge (Q80) for irrigation, the maximum available debit (Q80) can occur in November with 202,207 ltr / sec/ha and the minimum in August with 115,012 ltr / sec / Ha. Based on the results of the discharge and water above, it can be determined about the ratio of water/air equilibrium between discharge and water Q80 and the need for irrigation water requires a large/adequate surplus.